Understanding the origin, activation and regulation of matrix-producing myofibroblasts for treatment of fibrotic disease - Rafael Kramann; Derek P. DiRocco; Benjamin D. Humphreys (2013)
Fibrosis and scar formation results from chronic progressive injury in virtually every tissue and affects a growing number of people around the world. Myofibroblasts drive fibrosis, and recent work has demonstrated that mesenchymal cells, including pericytes and perivascular fibroblasts, are their main progenitors. Understanding the cellular mechanisms of pericyte/fibroblast-to-myofibroblast transition, myofibroblast proliferation and the key signalling pathways that regulate these processes is essential to develop novel targeted therapeutics for the growing patient population suffering from solid organ fibrosis. In this review, we summarize the current knowledge about different progenitor cells of myofibroblasts, discuss major pathways that regulate their transdifferentiation and discuss the current status of novel targeted anti-fibrotic therapeutics in development.